The acidic transcriptional activator GAL-VP16 acts on preformed template-committed complexes. - White, J (1992)
The action of the chimeric acidic transcriptional activator GAL-VP16 has been investigated by performing a series of kinetic experiments using the detergent Sarkosyl as well as monoclonal antibodies which specifically inhibit GAL-VP16 DNA binding and transcriptional activation. GAL-VP16 binds to recognition site rapidly, remains bound after transcriptional initiation and is required to maintain stimulated levels of reinitiation. GAL-VP16 action, which appears to result in an increase in the number of preinitiation complexes formed, occurs after the formation of template-committed complexes composed of promoter-bound TFIIA (STF) and a partially purified TFIID fraction conferring GAL-VP16 responsiveness on a reconstituted basal transcription system. This TFIID fraction cannot be replaced by TFIIB or cloned TFIID. Our results suggest that GAL-VP16 activates step(s) in preinitiation complex assembly occurring after TFIID has bound.